Pengaruh Brand Image, Atribut Produk dan Presepsi Kualitas Terhadap Keputusan Pembelian - Alfiana, Lela; Lukitaningsih, Ambar; Hatmanti, Lusia Tria (Jurnal Ilmiah Manajemen Kesatuan, 2021)
The research objective to be achieved is to analyze and explain the Brand Image, Product Attributes, Quality Perceptions of Purchasing Decisions in the People of Yogyakarta City. This research is a quantitative research. The population in this study were students of the Yogyakrta City Society. The data were collected by using a questionnaire method. The data analysis technique used is the validity test technique, the reliability of multiple linear regression which is supported by the t test, f test, and classical assumption test. The results of data analysis with a significance of 0.05 indicate that the variables brand image, product attributes, perceived quality have an effect on purchasing decisions Keywords: Brand Image, Product Attributes, Perceptions of Quality